Immune response and serum bactericidal activity against Brucella ovis elicited using a short immunization schedule with the polymeric antigen BLSOmp31 in rams. - Díaz, Alejandra Graciela (2013)
Brucella ovis is the etiologic agent of ovine brucellosis. The control measures for this disease are periodical diagnosis by serological tests and/or bacteriological culture and culling of positive animals. Vaccination with Brucella melitensis Rev 1 is recommended when prevalence is high. This attenuated strain vaccine gives protection against B. ovis but it has important disadvantages associated with the development of antibodies interfering with serodiagnosis, virulence for humans and the prohibition of its use in countries considered free of B. melitensis. Consequently, there is a need for new safe and effective brucellosis vaccines to be developed. We have previously reported that the polymeric subcellular vaccine BLSOmp31 confers protection against experimental challenge with B. ovis when rams are immunized three times. In the present work we evaluated and characterized, along 56 weeks after the first immunization of adult rams, the evolution of the immune response elicited by BLSOmp31 using a short immunization schedule.